INFLUENCE OF SOCIODEMOGRAPHIC FACTORS ON SEDENTARY BEHAVIOR IN ADOLESCENTS - Giulia Pacheco Souza; João Pedro Brant Rocha; Maria Clara Brant Rocha; João Gustavo Brant Rocha; Fernanda Piana Santos Lima de Oliveira; Ronilson Ferreira Freitas; Daniela Araújo Veloso Popoff; Josiane Santos Brant Rocha (PsychTech & Health Journal)
Sedentary behavior, intestinal constipation, and eating habits were examined concerning sociodemographic factors. A cross-sectional and analytical study was conducted with adolescents from municipal public schools in Montes Claros-MG, Brazil, through questionnaires investigating sociodemographic factors, pediatric gastrointestinal symptoms (Questionnaire Roma III), and eating habits (VIGITEL). Data were treated in the Statistical Package for Social Science program (version 22.0) through descriptive analysis of variables and the chi-square test. Of the 880 participants, the majority were female (51.93%) and aged between 13 and 19 (60.11%). A percentage of 16.7% exceeded 5 hours of sedentary behavior per day, and 15% were constipated. When comparing Sedentary Behavior with the sociodemographic profile, adolescent boys were more sedentary (p = .02), as were older adolescents (p = .01). In conclusion, there was a low prevalence of Sedentary Behavior, and the associations referred to sociodemographic factors. However, considering the studied population and the damage caused by sedentary behavior to the health of adolescents, these results are important to help in tracking this disorder.